2015
DOI: 10.1007/s00586-015-3992-0
|View full text |Cite
|
Sign up to set email alerts
|

Do in vivo kinematic studies provide insight into adjacent segment degeneration? A qualitative systematic literature review

Abstract: There appears to be no overall kinematic changes at the rostral or caudal levels adjacent to a fusion, but some patients (~20-30%) develop excessive kinematic changes (i.e., instability) at the rostral adjacent level. The overall lumbar ROM after fusion appears to decrease after a spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 81 publications
2
30
0
1
Order By: Relevance
“…Further, these protocols differ in the assumption on the postoperative motion behavior of the patients. In a parallel review on in vivo kinematics by Malakoutian et al [4], it was shown that the motion of the lumbar spine in patients tends to decrease after fusion in most studies, demonstrating that the notion that patients move the same after fusion as implemented with the stiffness and hybrid protocol does not appear to be correct. The decrease in motion shown in vivo could be predicted by the flexibility protocol.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, these protocols differ in the assumption on the postoperative motion behavior of the patients. In a parallel review on in vivo kinematics by Malakoutian et al [4], it was shown that the motion of the lumbar spine in patients tends to decrease after fusion in most studies, demonstrating that the notion that patients move the same after fusion as implemented with the stiffness and hybrid protocol does not appear to be correct. The decrease in motion shown in vivo could be predicted by the flexibility protocol.…”
Section: Discussionmentioning
confidence: 97%
“…For fusion procedures, it was shown in a parallel review article by Malakoutian et al that the cranial adjacent segment can be susceptible to the development of hypermobility in some cases, whereas at the inferior segment, either no changes were found or the motion decreased in the sagittal plane [4]. For total disc replacement (TDR) and other flexible implants, compensatory alterations in adjacent segments were seen rarely, apparently corroborating the protective potential of these devices.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent review article indicated that this may not represent the loading the DDD patients would experience in daily life and the normal controls and the DDD patients may perform this activity differently 24 . Therefore, future studies of DDD patients should be conducted under loading conditions experienced during typical daily activities such as walking.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the arthrodesis, motion will be lost at the operated motion segment, reducing the total cervical spine ROM. Thus, even if adjacent segment motion is equivalent after each procedure, motion segments adjacent to arthrodesis will appear to contribute more to the overall spine motion (in terms of percent of the total ROM) than motion segments adjacent to arthroplasty …”
Section: Cervical Spine Kinematicsmentioning
confidence: 99%